Postoperative complications in cleft lip and palate: a retrospective study at the General Hospital of México (2021-2023) - De Anda Hidalgo, Melissa; Chang, Emiliano O.; Corona, Maria Jose; Platas Galvan, Santos E.; Zamudio, Silverio Tovar (International Journal of Research in Medical Sciences, 2025)
Background: Cleft lip and palate (CLP) are among the most prevalent congenital malformations globally, with particularly high rates in low- and middle-income countries such as Mexico. While early surgical intervention can restore function and aesthetics, postoperative complications remain a clinical challenge. This study aims to identify the frequency and types of complications in patients referred to the General Hospital of Mexico between 2021 and 2023 following primary CLP surgery in other institutions. Methods: A retrospective review was conducted on 122 patients with CLP sequelae referred to the Plastic and Reconstructive Surgery Department at the General Hospital of Mexico from 2021 to 2023. Medical records were analyzed to determine the type and frequency of postoperative complications. Only patients with documented complications were included. Results: Among 122 cases, the most frequent complications were short lip (44.3%), palatal fistula (32.8%), and velopharyngeal insufficiency (19.7%). Less common issues included respiratory difficulty, lip paresthesia, dehiscence, and hypertrophic scarring (0.8% each). Complications were most often associated with patients undergoing both cheiloplasty and palatoplasty. Those with two surgeries had the highest relative risk for short lip (RR=4.0), velopharyngeal insufficiency (RR=2.2), and palatal fistula (RR≈1.92). Patients undergoing only one surgery had notably fewer complications. Conclusions: High-quality initial surgical repair is critical in preventing postoperative complications. Our findings highlight the importance of optimizing the first surgical intervention to reduce the need for additional procedures and improve long-term outcomes in CLP patients.